The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.1161/01.res.36.1.185
|View full text |Cite
|
Sign up to set email alerts
|

Dobutamine: development of a new catecholamine to selectively increase cardiac contractility.

Abstract: We systematically modified isoproterenol's chemical structure to reduce chronotropic, arrhythmogenic, and vascular side effects. Experiments on dogs showed that the resulting drug, dobutamine, had an inotropic efficacy as great as that of epinephrine due to a direct action on /?, cardiac receptors. However, unlike epinephrine, dobutamine's effect on a and ft, vascular receptors was slight. At equivalent inotropic doses, dobutamine had less than a fourth of the chronotropic effect of isoproterenol. Desmethylimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
173
2
13

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 603 publications
(200 citation statements)
references
References 27 publications
12
173
2
13
Order By: Relevance
“…In a whole animal, it was reported that dobutamine-induced cardiac effects were not influenced by desmethylimipramine, an uptake blocker of catecholamines (1). In the present study by use of isolated atria, we confirmed that dobutamine-induced positive chronotropic and inotropic effects were not modified by treatment with imipramine, although tyramine induced ones were markedly suppressed and dopamine-induced ones were slightly but significantly sup pressed as reported previously (9).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In a whole animal, it was reported that dobutamine-induced cardiac effects were not influenced by desmethylimipramine, an uptake blocker of catecholamines (1). In the present study by use of isolated atria, we confirmed that dobutamine-induced positive chronotropic and inotropic effects were not modified by treatment with imipramine, although tyramine induced ones were markedly suppressed and dopamine-induced ones were slightly but significantly sup pressed as reported previously (9).…”
Section: Discussionsupporting
confidence: 91%
“…administration of dobutamine to an intact animal produces a lesser increase in systemic blood pressure than that of dopamine (1,2). However, in isolated atria which were perfused with donor's blood, an i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another N-alkylated dopamine analogue, dobutamine, developed as an inotropic agent (Tuttle & Mills, 1975) is inactive as an agonist at vascular DA,-receptors (Robie et al, 1974) and at prejunctional DA2-receptors of the rabbit ear artery (unpublished observations), but is active in stimulating al-, PI-and P2-adrenoceptors (Maccarone et al, 1984).…”
Section: Discussionmentioning
confidence: 98%
“…Dopamine (DA) and dobutamine (DB) induce potent inotropic action through α and β adrenaline receptors on myocardial cell membrane [12,16,32]. However, CA may induce tachycardia and hypoxia in myocardium [33].…”
mentioning
confidence: 99%